Tending toward friendship: LGBTQ sexualities in US schools. (March 2019) - Gilbert, Jen; Fields, Jessica; Mamo, Laura; Lesko, Nancy
In 2014, Beyond Bullying, a research project examining LGBTQ sexualities and lives at school, installed private storytelling booths in three US high schools. Students, teachers, and staff were invited to use the booths to share stories about LGBTQ sexualities—their stories often invoked the pleasures and disappointments of being and having a friend. This article analyzes narratives of friendship as told in the Beyond Bullying storytelling booths. Drawing on Foucault's (1996) interview, 'Friendship as a way of life, ' we explore participants' stories of friendship as heralding 'new relational modes' that chart a liminal space between family and sexuality. These relational modes of friendship disrupt the familiar trope of the 'ally' in anti-bullying programs and complicate what empirical research on LGBTQ youth calls, 'peer social support.' Theorizing friendship allows LGBTQ sexuality in schools to reside in an ethics of discomfort, which accommodates complex social relations and varied forms of desire, intimacy, and yearning.